Endothelial alterations in a canine model of immune thrombocytopenia. (2nd January 2019) - LeVine, Dana N.; Cianciolo, Rachel E.; Linder, Keith E.; Bizikova, Petra; Birkenheuer, Adam J.; Brooks, Marjory B.; Salous, Abdelghaffar K.; Nordone, Shila K.; Bellinger, Dwight A.; Marr, Henry; Jones, Sam L.; Fischer, Thomas H.; et al.
Abstract: Bleeding heterogeneity amongst patients with immune thrombocytopenia (ITP) is poorly understood. Platelets play a role in maintaining endothelial integrity, and variable thrombocytopenia-induced endothelial changes may influence bleeding severity. Platelet-derived endothelial stabilizers and markers of endothelial integrity in ITP are largely underexplored. We hypothesized that, in a canine ITP model, thrombocytopenia would lead to alterations in the endothelial ultrastructure and that the Von Willebrand factor (vWF) would serve as a marker of endothelial injury associated with thrombocytopenia. Thrombocytopenia was induced in healthy dogs with an antiplatelet antibody infusion; control dogs received an isotype control antibody. Cutaneous biopsies were obtained prior to thrombocytopenia induction, at platelet nadir, 24 hours after nadir, and on platelet recovery. Cutaneous capillaries were assessed by electron microscopy for vessel thickness, the number of pinocytotic vesicles, the number of large vacuoles, and the number of gaps between cells. Pinocytotic vesicles are thought to represent an endothelial membrane reserve that can be used for repair of damaged endothelial cells. Plasma samples were assessed for vWF. ITP dogs had significantly decreased pinocytotic vesicle numbers compared to control dogs ( P  = 0.0357) and the increase in plasma vWF from baseline to 24 hours correlated directly with the endothelial large vacuole score ( R  = 0.99103; P  < 0.0001). This direct correlation between plasma vWF and the number of large vacuoles, representing the vesiculo-vacuolar organelle (VVO), a permeability structure, suggests that circulating vWF could serve as a biomarker for endothelial alterations and potentially a predictor of thrombocytopenic bleeding. Overall, our results indicate that endothelial damage occurs in the canine ITP model and variability in the degree of endothelial damage may account for differences in the bleeding phenotype among patients with ITP.